Multigene Phylogeny, Diversity and Antimicrobial Potential of Endophytic Sordariomycetes From Rosa roxburghii - Zhang, Hong; Wei, Tian-Peng; Li, Lin-Zhu; Luo, Ming-Yan; Jia, Wei-Yu; Zeng, Yan; Jiang, Yu-Lan; Tao, Guang-Can (Frontiers in Microbiology, 2021)
Rosa roxburghii Tratt. is widely applied in food, cosmetics, and traditional medicine, and has been demonstrated to possess diverse bioactivities. Plant endophytic fungi are important microbial resources with great potential for application in many fields. They are not only able to establish a mutualistic symbiosis with host plants but also to produce a variety of bioactive compounds. Therefore, in the present study, endophytic fungi were isolated from R. roxburghii. Molecular identification was carried out using protein-coding and ribosomal genes. Maximum likelihood analysis and Bayesian inference revealed the phylogenetic relationship of all endophytes. A total of 242 strains of endophytic Sordariomycetes were successfully isolated and identified. These isolates included 8 orders, 19 families, 33 genera. The dominant genera were Diaporthe (31.4%), Fusarium (14.4%), Chaetomium (7.9%), Dactylonectria (7.0%), Graphium (4.5%), Colletotrichum (4.1%), and Clonostachys (4.1%). The alpha diversity of different tissues, from high to low, were root, fruit, stem, flower, leaf, and seed. Functional annotation of 33 genera indicated that some fungi have multitrophic lifestyles combining endophytic, pathogenic, and saprophytic behavior. Additionally, antimicrobial activities were preliminarily screened. Dual culture test assay showed that there were 40 different endophytic species with strong inhibition of at least one or moderate inhibition of two or more against the 12 tested strains. Then intracellular and extracellular metabolites were prepared for these screened isolates, respectively. Subsequently, the re-screening assay was performed with the filter paper diffusion method. The results suggested that extracellular metabolites may be more advantageous than intracellular metabolites in the development of antimicrobial agents. From the perspective of the broad-spectrum and antimicrobial intensity, Hypomontagnella monticulosa HGUP194009 and Nigrospora sphaerica HGUP191020 were considered as isolates with good antimicrobial potential. Moreover, some fungi that caused disease had been observed to have beneficial biological activities as endophytic fungi. In conclusion, this study showed the species composition, alpha diversity, and lifestyle diversity of endophytic Sordariomycetes from R. roxburghii and demonstrated these isolates are potential sources for exploring antimicrobial agents.